An Anatomy of Faceted Search on World Wide Web - Yogesh,; Shalu,; Bhatia, Komal Kumar; Duhan, Neelam (International Journal of Computer Sciences and Engineering, 2019)
With rapid development of online web shops and E-commerce data, it is evident that users get convenience in different fields such as lexical similarity, Vocabulary mismatch, information retrieval etc. Faceted search is becoming a popular method to allow the user to interactively search in online web shops and product comparison sites. Trying to figure out retrieval of information using facet search to reduce the number of search results quickly to improve the search results. There are many attributes, for example, filter, facet value, facet and facet count, which can also be used for information retrieval towards the user search query. Over the years, all kinds of improve search results techniques have tried to simplify this task such as WebPT, NextGen and Kareo. This paper gives a detailed survey of some recent algorithms of faceted search, the attributes handled by them and the methods used by them.